Digital device use in managing unpaid care work : implications for the mental load of mothers in urban Colombo,Sri Lanka - Madumali, Wasala Mudiyanselage Naduni; Chatterjee, Joyee S.; Kusakabe, Kyoko; Hossain, Julaikha B.; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
This study examines how mothers in urban Colombo navigate the growing expectation to perform digital carework{u2014}the management of children{u2019}s educational, social, and daily needs through digital devices{u2014}within the broader landscape of unpaid carework. As smartphones, messaging applications, and online school platforms become central to children{u2019}s routines, mothers increasingly carry the cognitive, emotional, and managerial labour associated with both offline and online caregiving tasks. Drawing on in-depth interviews with 10 mothers who are full-time caregivers and those employed outside the home, the study explores how digital devices intensify mental load through continuous monitoring, information processing, anticipatory planning, and rapid decision-making. Guided by a gendered division of labour framework combined with the concept of mental load, the study analyses how digital engagement shapes the cognitive, emotional, and managerial dimensions of unpaid carework.The findings reveal that while digital tools can reduce aspects of unpaid carework by enabling reminders, improving coordination, and providing moments of respite or community support, they simultaneously extend the boundaries of carework into all times and spaces, creating expectations of constant availability. The invisibility of digital carework{u2014}often misinterpreted as leisure{u2014}further reinforces gendered social norms, as mothers remain the default point of contact for schools and households, with limited support from fathers. This research contributes to emerging discussions on the intersection of gender, technology, and unpaid labour by foregrounding the mental load generated through digital engagement and highlighting how digital carework reproduces, and in some cases reconfigures, existing inequalities in caregiving responsibilities.
A research study submitted in patial fulfillment of the requirements for the degree of Master of Science in Gender and Development Studies
Research (M. Sc.) - Asian Institute of Technology, 2025
Keywords: Wages -- Women -- Sri Lanka -- Columbo; Unpaid labor -- Sri Lanka -- Columbo